Application of Tchebichef moment in image watermarking techniques - ZHANG Li1; WEI Gang2; ZHANG Ji-hong1 (Tongxin xuebao)
A new way to enhance the robustness of watermarking is proposed by estimating the geometric distortions and enhancing parameters of corrupted watermarked image using Tchebichef moments of original image. Different watermarks are embedded into different original images in different domains including DWT, DCT, FFT and spatial domain. The geometric distortions are produced by Strimark. The computer simulation results show that the proposed method has a good robustness to Strimark and can be used in any domain. This method can be used as preprocess step of watermark detection and it is very useful to improve the processing robustness against geometric attacks of watermarking techniques.